“ESTUDIO SOCIOECONÓMICO DE LOS VENDEDORES Y SATISFACCIÓN DE LOS USUARIOS DE LAS FERIAS LIBRES, COMO CANAL TRADICIONAL DE COMERCIALIZACIÓN EN EL CANTÓN DE PINDAL, AÑO 2024” - JAYA ROMÁN, ANDREA ELIZABETH (2024)
Free fairs serve as an important channel for the direct sale of agricultural and artisanal products from small producers and local retailers. This allows consumers to access fresh, high- quality products at affordable prices. However, the socioeconomic conditions of vendors and user satisfaction indicate areas for improvement. The present research was carried out at the Pindal canton's free market in 2024, to evaluate the socioeconomic level of vendors, measure user satisfaction, and develop an improvement plan to optimize the fair's operation. A quantitative approach was adopted, with an exploratory-descriptive scope and a non- experimental design. Techniques such as direct observation, bibliographic research, interview, census, and survey were used. In addition, Microsoft Excel was used for coding and tabulation. The results indicated that more than 50% of the vendors are mestizo women with primary education, whose income varies between $40.00 and $310.00; they are self-employed and face expenses in food, health, transportation, and education. On the other hand, users highlighted quality, price, and customer service as the main reasons for preferring the fair as a traditional marketing channel. These findings have allowed the identification of aspects that require improvement; therefore, it is suggested to manage and implement an improvement plan that not only increases the satisfaction of users and vendors but also contributes to the socioeconomic development of the canton.